Surviving Tidal Tails Around the Milky Way Bulge Globular Cluster NGC 6355 - Piatti, Andres Eduardo (2024)
We present results of the analysis of a set of images obtained in the field of the Milky Way bulge globular cluster NGC 6355 using the Dark Energy Camera, which is attached to the 4 m Blanco telescope of the Cerro-Tololo Interamerican Observatory. We dealt with a heavy differential absorption across the observed field, a crowded field star population, and the superposition of field stars on to the cluster color–magnitude diagram main features to produce an intrinsic cluster stars density map. The resulting stellar density map reveals the presence of an extended envelope, a tidal tail, and scattered debris; the tidal tails pointing toward the Milky Way center. Such extra-tidal overdensities, detected above the mean star field density, resulted to be between four and six times larger that the local star field density fluctuation. They have also been recently generated by two independent studies which performed numerical simulations of synthetic tidal tails of Milky Way globular clusters. These results contrast with previous theoretical speculations about the possibility to detect tidal tails of globular clusters with chaotic orbits because they would be washed out after they were generated.